The Influence of Cultural Values on Perceptions of Corporate Social Responsibility: Application of Hofstede’s Dimensions to Korean Public Relations Practitioners - Kim, Yungwook (Journal of business ethics, 2010)
This study explores the relationship between Hofstede’s cultural dimensions and public relations practitioners’ perceptions of corporate social respon- sibility (CSR) in South Korea. The survey on Korean public relations practitioners revealed that, although Hofstede’s dimensions significantly affect public relations practitioners’ perceptions of CSR, social traditionalism values had more explanatory power than cultural dimensions in explaining CSR attitudes. The results suggest that practitioners’ fundamental ideas about the corporation’s role in society seem to be more important than their cultural values to understand public relations practitioners’ CSR attitudes in Korea.